2019
DOI: 10.1016/j.jtho.2019.09.189
|View full text |Cite
|
Sign up to set email alerts
|

P2.24 Lung Immune Prognostic Index in Patients with Non-small Cell Lung Cancer Treated with Either Chemo or Immunotherapy

Abstract: Background: To characterize and identify factors associated with the presentation of hyperporgression after initiation of immunotherapy in patients with advanced non-small cell lung cancer (NSCLC). Method: A multicenter international retrospective study on 110 patients was conducted. Clinical variables as well as routine blood studies were recorded before initiation of treatment. Regression analysis was used to find associations. A random forest tree analysis (RFTA) based on continuous and discrete variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The numbers of patients treated with ICI, TT, and CT were 3,651, 1,241, and 2,481, respectively. We also provided the information of the median OS and 95% CI of 2,048 patients who did not meet the inclusion criteria under different treatment methods [5,6,10,[16][17][18][19][20]. Characteristics of the included studies are shown in Table 1, and characteristics of patients in other literature that did not meet the inclusion criteria are given in Table 2.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The numbers of patients treated with ICI, TT, and CT were 3,651, 1,241, and 2,481, respectively. We also provided the information of the median OS and 95% CI of 2,048 patients who did not meet the inclusion criteria under different treatment methods [5,6,10,[16][17][18][19][20]. Characteristics of the included studies are shown in Table 1, and characteristics of patients in other literature that did not meet the inclusion criteria are given in Table 2.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%